Effectiveness of the Community Empowerment Program (PRODAMAT) in Improving Larval Monitoring Cadres’ Knowledge of Dengue Prevention in Bokoharjo Village - Agusalim, Nurham Al-Afgani; Arfiana, Rizkita; Mursalina, Gesti; Adila, Lutfi Munifah; Sholiah, Dwi Yuliatin; Izzah, Misyka Fajratul; Hayyusari, Meirsa Sawitri; Sulistyawati, Sulistyawati (Reflection Journal, 2026)
The Community Empowerment Program (PRODAMAT) was implemented to strengthen the role of larval monitoring cadres (Jumantik) in dengue prevention through a community-based educational approach. This study aimed to evaluate the effectiveness of the intervention in improving cadres’ knowledge of dengue prevention, particularly through the PSN 3M Plus strategy. A pre-experimental one-group pretest-posttest design was employed involving 24 Jumantik cadres in Bokoharjo Village, Prambanan District, Sleman Regency, Yogyakarta. The intervention consisted of interactive offline health education supported by PowerPoint-based materials covering dengue epidemiology, mosquito life cycles, and larval identification techniques. Knowledge was measured using pre-test and post-test questionnaires, and data were analyzed using the Shapiro-Wilk normality test and paired samples t-test. The results showed that the mean knowledge score increased from 21.71 before the intervention to 23.50 after the intervention, with a statistically significant difference (t = -5.840; p < 0.001). These findings indicate that the educational intervention was effective in improving the cognitive capacity of Jumantik cadres regarding dengue prevention. However, increased knowledge alone may not ensure sustained preventive behavior without continuous supervision, motivation, and program support. Therefore, integrating community education with routine monitoring and public health surveillance is necessary to achieve long-term epidemiological outcomes, including improvement in the Larvae-Free Index.